TATA KELOLA PERUSAHAAN, ALIRAN KAS BEBAS DAN MANAJEMEN LABA - FLORENCIA FLORENCIA; MEINIE SUSANTY (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2019)
The purpose of this study is to examine the factors that influence earnings management on non financial companies that listed in Indonesia Stock Exchange. These factors are firm size, audit quality, audit committee, institutional ownership, return on assets, leverage, and free cash flow. Population of this research are non financial companies listed in Indonesia Stock Exchange from 2015-2017. The samples of this study are selected by using purposive sampling method and 558 data are taken. This research used a modified Jones model to calculate discretionary accruals values. This research used multiple regression analysis to determine the relationship between the factors and earnings management. The result of this study shows that return on assets, leverage, and free cash flow have effect on earnings management. On the other hand, firm size, audit quality, audit committee, institutional ownership do not have significant effect on earnings management.